Lipid profile in children with overweight and obesity: an integrative review (Research, Society and Development, 2020)
Introduction: Childhood and juvenile obesity has grown significantly in the world in recent decades and is strongly associated with several metabolic abnormalities, such as: glucose intolerance, arterial hypertension and dyslipidemia, being also major factors for the development of cardiovascular diseases and diabetes II. Objective: To identify the lipid profile of overweight and obese children and adolescents and to verify the association with cardiometabolic diseases. Methodology: This is an integrative literature review, where it was carried out by means of electronic search in the PubMed, BIREME and SciELO databases, from September to October 2019. 255 articles were identified and, through eligibility criteria, a total of 18 were selected at the end. Results: The results of the biochemical analyzes of the articles studied confirm the hypothesis that metabolic changes are already present in childhood and adolescence. Conclusion: The scientific literature presents several studies in which children and adolescents with overweight and obesity have increased concentrations of circulating lipids, and affirm a higher prevalence of dyslipidemia, when compared to eutrophic.